Impact of Low doses of Gamma Irradiation on Shelf life and Chemical Quality of Strawberry (Fragariaxananassa) cv. ‘Corona’ - A. Majeed; Z. Muhammad; A. Majid; A.H. Shah; M. Hussain (Journal of Animal and Plant Sciences, 2014)
Post-harvest quality losses of fruits and vegetables during storage are global horticultural problems. The use of synthetic chemicals and fumigation to minimize such losses and to extend shelf life of fresh produce are primarily effective strategies; however they are vigilantly accepted by consumers because of potential health risks and environmental problems they pose. The aim of this study was to evaluate gamma irradiation doses 0.5, 1.0 and 1.5 kGyfor their effect on shelf life and chemical attributes of Strawberry (Fragariaxananassa) cv. Corona stored for nine days at room temperature. Berries irradiated with 1.0 and 1.5 kGy showed significantly prolonged storage life (5.75 and 7.75, days respectively) when compared to non-irradiated control fruits (3.25 days). Non-radiated fruit samples showed maximum decay (94.5 %) and weight loss (58 %) at 9th day of storage; however, irradiation significantly reduced these two quality parameters especially at higher doses which corresponded to lower weight loss and fruit decay. Neither radiation treatment nor storage period had significant effect on total soluble solids, titratable acidity and pH of fruits. Results indicated that radiation doses 1.0 and 1.5 kGymight be used as consumers’ acceptable doses for shelf life extension, minimum weight loss and decay, without affecting the chemical quality of strawberry.
Keywords: Ionizing radiation; microbial disinfection; titratable acidity; total soluble solids